An Exploratory Study of the Key Strategic Decision Making Characteristics and Processes that drive Emerging and Global Fintech (Financial Technology) Companies - Furusa, Tatenda M L (2017)
The last decade has seen the rapid rise of the phrase “fintech”, short for financial technology. According to an Accenture 2015 report, global investment in Fintech has ballooned from $USD 930 million in 2008 to over $USD 12 billion by 2015 and European fintech growing by up to 215%. Fintech is changing the way consumers interact with financial services and how traditional institutions operate on a day to day basis. Some of the disrupted areas include mobile payments, insurance, loans and banking. For example, consumers can now access loans much quicker and faster or send money across borders at relatively low costs too. For companies the traditional brick and mortar operation has been abandoned allowing them to deliver services with limited overheads. In such a hyper competitive and fast growing sector, the importance of making the right strategic decisions can make or break the survival of a company. Therefore, this study aims to explore the key strategic decision making characteristics of emerging and established fintech companies and draw comparisons and insights into how they formulate and implement plans. As a qualitative study, semi-structured interviews were conducted with middle to senior managers of seven fintech companies. The objectives were to understand what methods and processes were adopted by some of the leading fintech firms and especially formal versus flexible strategic planning, methods of market scanning and the ability to adapt to an ever changing external environment. In addition, the role of innovation in strategy and whether strategic decisions differed from location to location was explored. It was analysed that most companies adopted some semblance of formal planning and review but were steering more towards a tactical and iterative planning approach based upon the fast changing environment. Furthermore, it was confirmed that those firms that encouraged innovation over strategy were more agile and responsive to the market needs than those who did not. However, strategic decisions in terms of new market expansion were also influenced by key stakeholders such as clients and group led factors often meaning that future plans were pre-determined. The main basis for the findings provided thought leadership on how fintech companies can simultaneously be embedded with a long term vision but still successfully grow by adopting an industry specific set of best practice processes that navigate today’s high velocity and competitive environments.